PERAN LINGKUNGAN PERTEMANAN DALAM MEMBENTUK KEHIDUPAN REMAJA - Juwinner Kasingku; Winda Novita Warouw (Yayasan Nusantara Hasana Berdikari, 2026)
Adolescence is an important stage in life because it is during this period that individuals begin to form their identity. One of the most influential factors is the social environment, especially friendships. This study aims to understand how friendships influence the life values of adolescents. The method used is a Systematic Literature Review which involves collecting and analysing various scientific articles from journals over the past 10 years through Google Scholar and other reliable sources. The results show that friendships have two types of impact. The positive impacts include helping adolescents build self-confidence, learn cooperation, and gain emotional support. However, there are also negative impacts such as peer pressure, deviant behaviour, bullying, and mental health issues like stress or depression. These influences become even stronger in the digital era through social media. In conclusion, friendships have a significant influence on adolescents' lives. Therefore, adolescents need to choose their friends wisely and have strong life principles. In addition, parents and teachers also play an important role in guiding and setting good examples so that adolescents can develop positively.